NILAI PERUSAHAAN YANG DIPENGARUHI OLEH LIKUIDITAS DAN KEPEMILIKAN INSTITUSIONAL (Survey Pada Perusahaan Sektor Barang Konsumsi Primer Yang Terdaftar Pada Bursa Efek Indonesia Periode 2017-2021) (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2023)
This study aims to determine how much the firm value is influenced by liquidity and institutional ownership in Primary Consumer Goods Sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. The problem that occurs in primary consumer goods sector companies is the decline in company value even though liquidity and institutional ownership have increased. The method used in this study is a descriptive verification method with a quantitative approach, the sample used in this study is 43 companies in the Primary Consumer Goods sector listed on the Indonesia Stock Exchange for the 2017-2021 period with a 5-year observation period, so the total unit of analysis is 215. The analytical tool used is multiple linear regression, coefficient of determination, correlation coefficient, and T-test. The results of the study show that (1) Liquidity has a positive significant effect on firm value, and (2) institutional ownership has a positive significant effect on firm value..